Five-year follow-up of Japanese patients with Paget's disease of the bone after treatment with low-dose oral alendronate: a case series - Iba, Kousuke (BioMed Central, 2010)
INTRODUCTION: Paget's disease of the bone is characterized by focal abnormalities of increased bone turnover affecting one or more sites throughout the skeleton. Although this disease is rare in Japan, it is common in western and southern Europe, and among British migrants in Australia and New Zealand. Bisphosphonates have been widely used for the treatment of Paget's disease of the bone and are considered to be the treatment of choice. However, there have been few reports on the long-term follow-up examination of patients after their treatment with bisphosphonates. CASE PRESENTATION: We report the treatment with a low dose of oral alendronate (5 mg per day) which was effective in reducing bone turnover and pain over the five-year follow-up period in two Japanese patients, a 66-year-old man and a 68-year-old woman, with Paget's disease of the bone. Furthermore, in one patient, no clinical symptoms, such as bone pain or increases in serum total alkaline phosphatase and urinary N-terminal telopeptide of type I collagen as markers of bone turnover, were observed over the patient's five-year follow-up period. CONCLUSIONS: To the best of our knowledge, this is the first report of a long-term follow-up of patients with Paget's disease of the bone after a six-month treatment with low-dose oral alendronate (5 mg per day).